IMMUNOSTIMULANT EVALUATION OF NEEM LEAVES AGAINTS NON-SPECIFIC IMMUNE OF TILAPIA INFECTED BY A. hydrophila - Islamy, R A; Hasan, V; Mamat, N B; Kilawati, Y; Maimunah, Y (Iraqi journal of agricultural science, 2024)
The aim of this study was to find out how neem leaf extract affected the immune systems of Tilapia (O. niloticus) that had A. hydrophila in their bodies. This included looking at its phytochemistry, antibacterial properties, bioactive compounds, and ability to make the immune system stronger. The extraction uses methanol. The phytochemical test of neem leaf extract includes flavonoids, alkaloids, tannins, saponins, and triterpenoids. We obtained the isolate A. hydrophila from the Jepara Brackish Water Aquaculture. Before use, we store these bacteria in Trypticase Soy Agar (TSA) media at 4 oC and Trypticase Soy Broth (TSB) subcultures. re use.       Test antibacterial using published We confirmed flavonoids, tannins, saponins, and triterpenoids through phytochemical tests. firmed.       The test against A. hydrophila bacteria found that 100% of the extract was the most effective concentration at stopping the growth of A. hydrophila bacteria. After feeding A. hydrophilla bacteria to Tilapia (O. niloticus), the extract of neem leaf (A. indica) significantly boosted the immune system. bserved.